Analyzing the Relationship Between Deforestation and Climate Change Using Satellite Data; International Journal of Computations, Information and Manufacturing; Vol. 4, No. 2 - Vorobyeva V. V. Viktoriya Vladimirovna (2024, 2024)
Title screen